Literary-Critical Studies in the Gilgamesh Epic: An Assyriological Contribution to Biblical Literary Criticism - Tigay, Jeffrey
PhD Diss.; Supervisor: W. W. Hallo; Order No. 72171880; Revised version about to appear with University of Pennsylvania Press; completes.